1984
DOI: 10.1128/iai.43.3.1106-1109.1984
|View full text |Cite
|
Sign up to set email alerts
|

Transport of glucose and mannose by a common phosphoenolpyruvate-dependent phosphotransferase system in Streptococcus mutans GS5

Abstract: Decryptified cells of Streptococcus mutans GS5 transport glucose, mannose, and fructose by constitutive phosphoenolpyruvate-dependent phosphotransferase systems (PTSs). Although the non-metabolizable glucose analog 2-deoxyglucose is transported by a PTS, a-methylglucose is not taken up by strain GS5. The transport of [14C]mannose and ['4C]glucose was almost totally blocked by the heterologous sugars, indicating that these substrates may share a common PTS permease. [14C]fructose transport, however, was not inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…Moreover, whole cells of the mutant strains were able to accumulate glucose under conditions that inhibit active transport mechanisms other than the PTS, but were defective in their ability to accumulate 2DG, a mannose analogue. Since it has already been shown that EII""'" can also phosphorylate glucose (13,39), results presented in this paper indicated that S. mutans and S. sobrinus possess two distinct PTS that could phosphorylate glucose as we have already suggested in the past (39). It thus appears that lactic and oral streptococci have different PTS structures.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Moreover, whole cells of the mutant strains were able to accumulate glucose under conditions that inhibit active transport mechanisms other than the PTS, but were defective in their ability to accumulate 2DG, a mannose analogue. Since it has already been shown that EII""'" can also phosphorylate glucose (13,39), results presented in this paper indicated that S. mutans and S. sobrinus possess two distinct PTS that could phosphorylate glucose as we have already suggested in the past (39). It thus appears that lactic and oral streptococci have different PTS structures.…”
Section: Discussionsupporting
confidence: 64%
“…The carbohydrates glucose, fructose and mannose are PTS sugars in Grampositive streptococci (13,30,31,33,39). However, information concerning the number and the nature of the specific components involved in the transport of these sugars is scarce, and sometimes conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly suggest that the abovedescribed activities are all due to a single constitutive PTS, i.e., Man-PTS, a nomenclature after the similar constitutive PTS of enterobacteria (10). Man-PTS with a similar substrate specificity has also been described for other lactic acid bacteria (2,6,8,9,17). Strain LAC 12 showed no PTS activity for methyl-a-D-glucoside, indicating that the strain has no "Glc-PTS" known in enterobacteria (10).…”
mentioning
confidence: 55%
“…In streptococcal cells only the presence of the mannose/glucose/2-deoxyglucose permease has been established [26,27]. There are conflicting reports about the presence of an additional glucose/a-methylglucoside transport system in oral streptococci [28,29]. Similarly,, III gl~, involved in the uptake of glucose/a-methylglucoside in Gram-negative bacteria, has not been detected in Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 99%